Ruang Lingkup dan Karakteristik Hukum - Wahyu Safitri (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The existence of law within a state is one of the fundamental aspects and not merely a formality of the state. Law has a very significant function and influence, both in creating justice, order, protection of human rights, and welfare. Indonesia is one of the countries that has legal pluralism, namely customary law, Islamic law, and national law. These three legal systems are important components in every agenda for the formulation and creation of laws in Indonesia. The tendency of legal characteristics includes regulating societal behavior, being coercive and binding, containing prohibitions and commands. Its purpose is to regulate behavior and relationships among humans. Thus, justice, harmony, and social order are created.